A New Approach to Investigate Thin Surface Layers of Polymers: Fatigue Analysis of Polycarbonate. Issue 4 (April 2013) - Nagai, Naoto; Nishiyama, Itsuo; Shimada, Hideo; Ito, Hidemi; Endo, Kazunaka
A new technique to investigate chemical structures of very thin surface (mesoscopic scale) layers of polar polymers is proposed. The chemical structures and conformations of 100 nm-thick slabs that were obtained from a polymer surface were studied by infrared spectroscopy combined with a previously developed thin sample preparation system. The dielectric functions were calculated using oscillator models from reflection spectra of the slabs, which were cut with a diamond blade. The molecular movements caused by shear force perturbations after the cutting process ("flexed state") were observed. The technique was applied to analyze the changes in the chemical structure of bisphenol A polycarbonate (BPAPC) throughout a bending cyclic fatigue test. Three characteristic stages of structural changes in the flexed state under the cyclic fatigue test were observed. Our technique has the potential to clarify the intrinsic structures of solid polymers such as the degree of entanglement and the tendency for order or disorder caused by the surrounding chain interaction.